Use of Boelen’s conceptual model to develop a portrayal of the evolution of social accountability at a Canadian medical school - Cumyn, Annabelle; Hatcher, Sharon; Larouche, Catherine; Dubé, Tim; Millette, Charles-Antoine; Landry, Michel; Gagné, Ève-Reine (Canadian Medical Education Journal, 2024)
Background: Social accountability (SA) takes an important place in the accreditation requirements of Faculties of Medicine. We analyzed the evolution of SA in the undergraduate medical program at the University of Sherbrooke since the implementation of a complete curriculum in two distributed medical campuses. Methods: Using a qualitative and sequential research design anchored in Boelen's conceptual framework, we conducted a document analysis of strategic plans and accreditation documents between the years 2006-2023 to identify the SA actions of the medical program and generate an initial narrative with a timeline. Following three interviews and three focus groups with key actors at each campus, we developed a final portrayal of SA with a timeline. Results: The portrayal describes the way in which the faculty and its medical program planned their commitment in line with the identified health needs of the population (conceptualization), implemented actions to meet these needs (production) and verified that these actions “have had the greatest possible impact on people’s health” (usability). This approach demonstrates the time required to observe an increase in actions related to usability. Conclusions: This study made it possible to identify the work accomplished since 2005 by highlighting the strengths and challenges. This understanding of the road traveled, and the challenges encountered, will be shared with partners to identify further actions in response to the health needs of communities served. This approach and the resulting findings may serve as a source of information for other faculties of medicine interested in undertaking an analysis of their social accountability actions.